2014
DOI: 10.1007/s11164-014-1873-5
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of pyran annulated heterocyclic scaffolds: a highly convenient protocol using dimethylamine

Abstract: A facile and rapid three-component synthesis of pharmaceutically diverse pyran annulated heterocycles has been developed via a one-pot condensation of aromatic aldehydes, malononitrile, and different enolizable C-H-activated acidic compounds in the presence of dimethylamine as a newer and effective organo-catalyst in ethanol under mild reaction conditions. Selectivity of various pyran derivatives depends on the structure of enolates. The present protocol has synthetic advantages of excellent yields in much sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(5 citation statements)
references
References 30 publications
0
3
0
2
Order By: Relevance
“…The pyranopyrimidines were synthesized in 87-95% yields, in which the yields of the products were developed than the previously reported methods for the synthesis of these compounds. 24,26,[54][55][56][57] Amirnejat et al 58 reported the synthesis of these bicyclic systems 10a-c under the catalytic conditions of BaFe 12 O 19 @IM nanocomposite. The nanocatalyst was prepared by the reaction of barium nitrate with iron(III) nitrate nonahydrate, and citric acid in distilled water in an ultrasonic bath for 15 min, subsequently it was treated with ammonia solution (pH ¼ 8) to generate barium hexaferrite nanoparticles.…”
Section: Synthesis Of Bicyclic Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…The pyranopyrimidines were synthesized in 87-95% yields, in which the yields of the products were developed than the previously reported methods for the synthesis of these compounds. 24,26,[54][55][56][57] Amirnejat et al 58 reported the synthesis of these bicyclic systems 10a-c under the catalytic conditions of BaFe 12 O 19 @IM nanocomposite. The nanocatalyst was prepared by the reaction of barium nitrate with iron(III) nitrate nonahydrate, and citric acid in distilled water in an ultrasonic bath for 15 min, subsequently it was treated with ammonia solution (pH ¼ 8) to generate barium hexaferrite nanoparticles.…”
Section: Synthesis Of Bicyclic Systemsmentioning
confidence: 99%
“…The pyranopyrimidines were synthesized in 87–95% yields, in which the yields of the products were developed than the previously reported methods for the synthesis of these compounds. 24,26,54–57…”
Section: Synthesis Of Bicyclic Systemsmentioning
confidence: 99%
“…[12][13][14][15] 4-(N,N-Dimethylamino)pyridine (DMAP) can promote a number of organic transformations as a reusable catalyst, [16][17][18] and the combination of an MCR approach with organocatalysis has proved to be a most effective strategy. 19 In a continuation of our current work devoted to the synthesis of medicinally important heterocycles by using green solvents or catalysts, [20][21][22][23][24][25][26][27][28][29][30] R. Ramesh et al…”
mentioning
confidence: 99%
“…Aplicação/Referência Atividade antibacteriana Kumar et al [6] Atividade antimicrobiana Behbehani et al [7] Atividade antimicrobiana Al-Mousawi et al [8] Inibidor da enzima αglucosidase Kashtoh et al [9] Antidepressivo Mishra et al [10] Tratamento de câncer Ramesh et al [11] Diversos autores já descreveram um número significativo de metodologias sintéticas usando diferentes condições de reação, diferentes tipos de bases [16], ácidos de Lewis [17], catalisadores metálicos [18], fibras sintéticas [19], uso de ultra-som [20] ou polímeros [21].…”
Section: Reaçãounclassified
“…g.L -1 ), H3BO3 (0,030 g.L -1 ) em pH 8. trabalhos que relataram esta síntese de duas maneiras diferentes: via reação bicomponente [8,9] ou via reação tricomponente (one-pot) [10,11,12] Quanto a natureza do núcleo aromático presente (benzenoide ou furano) foi constatado um aumento no valor de rendimento isolado para o composto contendo o anel furano (54% para 3j) em relação ao núcleo benzênico (44% para 3a). Este aumento no rendimento pode ser justificado devido ao menor efeito de ressonância observado no anel furano em comparação ao anel benzeno, devido a presença do oxigênio como heteroátomo, o qual por sua vez é altamente eletronegativo e não disponibiliza facilmente seu par de elétrons para realizar ressonância por toda molécula.…”
Section: Biotransformação Dos Adutos Deunclassified